AB0353 Genetically predisposition and pro-inflammatory dysregulations – connecting rheumatoid arthritis and mental disorders. (12th June 2018) - Filipescu, I.C.; Ghib, L.; Juan Sainz, P.; Perez-Sanchez, C.; Lopez-Pedrera, C.; Escudero, A.; Damian, L.; Muntean, L.; Collantes-Estévez, E.; Rednic, S.
Abstract : Background: Depressive and anxiety disorders are reported as the more prevalent psychiatric comorbidities in chronic inflammatory diseases and their occurrence has been correlated with higher serum levels of cytokines and chemokines (IL-6, IL-1, IL-12, IL-18, TNF-α, and even TNF-RI and TNF-RII). Some single nucleotide polymorphisms (SNPs) in TNF-α gene have been found to play a common part in pro-inflammatory alterations in patient with rheumatoid arthritis (RA) and depressive symptoms. Objectives: To investigate the possible influence of four single-nucleotide polymorphism in the tumour necrosis factor receptor II (TNFRII) genes and development of psychiatric disorders in patients with active RA. The second aim was to evaluate some correlation between these SNPs, the level of four chemokines and the incidence of mental disorders. Methods: We included 89 Caucasian patients with active RA treated in a tertiary Department of Rheumatology from Cluj-Napoca. All demographic, clinical, and biological data and RA comorbidities were completed. The presence of depressions or anxiety was confirmed at the baseline by psychiatrist. Four potentially functional SNPs within TNFRSF1B (rs1061622, rs1062624, rs1061631, rs3397) were selected to be genotyped in all patients using PCR (KASPar) asASys (KBiosciences, Hoddesdon, Hertfordshire, UK) at the Centre for Genomics and Oncological Research (GENYO), Granada, Spain. Plasmatic levels of soluble tumour necrosis factor receptor II (sTNFRII), interleukin (IL)−6, monocyte chemotactic protein (MCP)−1 and vascular endothelial growth factor (VEGF was quantified using cytofluorometry-based ELIAS technique in accordance with manufacturer's instructions using FlowCytomix kit (eBioscience, UAS) at Instituto Maimonides de Investigacion Biomedica de Cordoba – Reina Sofia Hospital, Spania. Results: According to DAS28 (CRP) all the patient have active arthritis (5.87±0.6) with median disease duration of 9 (4–14) years. Most of the patients were diagnosed with depression (n=33), 84.8% were female. Anxiety was present at 21 subjects (80.9% female). In 3 cases these two mental disorders coexist. In a subgroup with depression the polymorphism rs1061631 (GG) was significantly associated with increased level of VEGF (p=0.007). A significant correlation was also found between the polymorphism rs3397 (CC/TT) and MCP-1 level (p=0.01). In a subgroup with anxiety the significant association was found between the polymorphism rs1061631 (GG) and the level of MCP-1 (p=0.04). Conclusions: Pro-inflammatory dysregulation might be particularly relevant in some patients with RA and psychiatric illness. Amongst genetic factors that influence the susceptibility to the development of RA and psychiatric disorders some single nucleotide polymorphisms (SNPs) in TNF-α gene have been considered with increasing interest. Further investigation in a larger cohort is needed. Disclosure of Interest: None declared